Natural capital accounting reveals ecosystems’ role in water and energy security in Colombia’s Sinú Basin - Lisa Mandle; Héctor Angarita; Jaime Moreno; Jesse A. Goldstein; Sioux F. Melo L; Alejandra Echeverri; Nicolas Rojas; Fabián Dario Villalba (Communications Earth & Environment)
Abstract Many valuable economic benefits from nature have traditionally been overlooked in both national accounts and government policy. To remedy this, countries are adopting the new United Nations System of Environmental-Economic Accounting framework for valuing ecosystem services, but inclusion of key hydrological services has so far been limited. Here we develop ecosystem service flow accounts linked to a natural capital assessment in Colombia’s Sinú Basin to value ecosystems’ contributions to water and energy security. Using integrated biophysical and economic models parameterized with local data, we find ecosystems deliver sediment retention benefits to the energy and water sectors equivalent to 1.7% of the region’s gross domestic product. A planned expansion of the region’s aqueduct system would further increase these services’ value by 12%. Our findings are informing development planning and policy within Colombia and provide lessons for the many other countries adopting natural capital accounting to support their sustainable development goals.